Defining the meiotic functions of the checkpoint protein DPB11 - Garnell, Thomas (2024)
DNA damage repair checkpoints identify unrepaired DNA double-strand breaks (DSBs), activating checkpoint kinase Mec1, typically with its accessory protein Dpb11, alongside various downstream effectors responsible for halting cell cycle progression. Recent work has identified Dpb11 dependent (Mordes, Nam and Cortez, 2008) and independent (Navadgi-Patil and Burgers, 2009) functions of Mec1 during mitosis. During the initial stage of meiosis, a specialised cell cycle state that generates haploid gametes from a starting diploid cell, DSBs are introduced throughout the genome, some of which repair as crossover events linking homologous chromosomes. Previous work has shown that not only does Mec1 undertake a checkpoint function inhibiting entry into the first meiotic division until DSBs are repaired, but it also stimulates DSB break formation and instigates interhomolog biased repair. Our work aims to investigate Dpb11’s currently undefined roles during meiosis and explore the requirements of Dpb11 in Mec1 activity. To accurately characterise the meiotic phenotype of removal of Dpb11, we created Dpb11 and Mec1 meiotic depleted (dpb11-md/mec1-md) strains by placing the expression of these genes under the Clb2 promoter, known only to be expressed outside of meiosis. In addition, we created N and C terminally 6His-3HA tagged Dpb11 and Mec1 to investigate protein expression and potential post-translational modifications (PTMs). Characterisation of meiotic depleted strains via spore viability and sporulation efficiency indicate roles of Mec1 both dependent and independent on Dpb11. Analysis of tag-dpb11 and dpb11-tag strains indicated that C-terminus and N-terminus tags do not impair potential Dpb11 activity during meiosis. The meiotic phenotype of tag-dpb11-md and dpb11-tag-md indicates that integration of the PCLB2 has impacted Dpb11s expression; however, to what extent remains unclear. Our data suggests that Dpb11 has independent roles from Mec1 as the addition of a dpb11-md mutation into mec1-md strains showed a difference in spore viability and sporulation efficiency compared to single mec1-md strains. It remains unclear if Dpb11 has any roles dependent on Mec1 due to variation between the dpb11-md mec1-md double mutant meiotic phenotypes. Finally, mec1-md had lower spore viability and sporulation efficiency when compared to the dpb11-md strains, suggesting that Mec1 has roles that are not dependent on Dpb11 during meiosis.